Kandungan Proksimat dan Daya Pengikatan Tepung Iles-Iles (Amorphophallus oncophylus) Terhadap Aflatoksin Sebagai Upaya Pencarian Bahan Pengikat Alternatif pada Pakan - Sigit Hananto; Sri Pujiyanto; Endang Kusdiyantini (Jurnal Akademika Biologi, 2015)
Aflatoxin  is  a  metabolite  secondary  of  Aspergillus  flavus  and  A.  Parasiticus. Contamination  aflatoxin in poultry have an impact on their liver damage. Technique to reduce the effects of aflatoksin can be done by addition of aflatoxin binder. Aflatoxin binder material commonly used still import as  glucomannan yeast product (GYP), so we needed study local material that has the potential  as a a  aflatoxin binder. The purposes is  test proximate content and the binding power of flour iles-iles compared  to GYP. Sample in research  is  flour  derived  from  bulbs  iles-iles  (Amorphophalus  oncophylus)  and  GYP  as control. The parameters in research that is the physical characteristics , proximate analysis , glukomannan levels and the ability of binding aflatoksin in vitro between flour iles-iles and GYP. The results of the physical test, the sample has delicate texture and gross energy flour iles-iles not significantly different with GYP. The results of proximate analysis ( the water level , ashes , crude fiber , crude protein and crude fat) show between flour iles-iles and GYP was significantly different, except crude fat that shown the result is no different (p<0,05) .The results of the analysis in the glukomannan levels of flour iles-iles is 52,74 % and GYP 17,36%. Testing the ability bind done with a solution of aflatoksin 2 ml (2.7 ng/ml) and materials binder used is 0  g; 0,0013 g; 0,0027 g and 0,0040 g. The research results show binding aflatoxin by flour iles-iles optimal in heavy 0,0013 g (92,92 %), while binding aflatoxin by GYP optimal in heavy 0,0040 g (87,71 %). The ability binding aflatoksin flour iles-iles in proportion to GYP so that can be used as a alternative binder in feed. Keyword: Iles-iles (Amorphophallus oncophylus), aflatoxin, Glucomannan